Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/fbp.0000000000000224
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine-like discriminative stimulus effects of bupropion and its two hydroxy metabolites in male rhesus monkeys

Abstract: The dopamine transporter (DAT) inhibitor and nicotinic acetylcholine (nACh) receptor antagonist bupropion is being investigated as a candidate ‘agonist’ medication for methamphetamine addiction. In addition to its complex pharmacology, bupropion also has two distinct pharmacologically active metabolites. However, the mechanism by which bupropion produces methamphetamine-like ‘agonist’ effects remains unknown. The present aim was to determine the role of DAT inhibition, nACh receptor antagonism, and the hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Based simply on the close genetic homology of NHPs to humans [59], it is reasonable to expect they would be a superior translational model to understand bupropion CNS disposition and ensuing central effects in humans. However, in vitro metabolite kinetics, and 15 in vivo metabolite disposition in NHPs is limited [51,[60][61][62], and reports of stereoselective analysis are absent. We found that the total percentage of hydroxybupropion, threohydrobupropion, erythrohydrobupropion in marmoset monkey liver microsomes (62%, 23%,14%, respectively) is in good agreement with a previously published report (62%,28%,10%) in baboon hepatic microsomes [60].…”
Section: Discussionmentioning
confidence: 99%
“…Based simply on the close genetic homology of NHPs to humans [59], it is reasonable to expect they would be a superior translational model to understand bupropion CNS disposition and ensuing central effects in humans. However, in vitro metabolite kinetics, and 15 in vivo metabolite disposition in NHPs is limited [51,[60][61][62], and reports of stereoselective analysis are absent. We found that the total percentage of hydroxybupropion, threohydrobupropion, erythrohydrobupropion in marmoset monkey liver microsomes (62%, 23%,14%, respectively) is in good agreement with a previously published report (62%,28%,10%) in baboon hepatic microsomes [60].…”
Section: Discussionmentioning
confidence: 99%